2007
DOI: 10.1002/elps.200700139
|View full text |Cite
|
Sign up to set email alerts
|

Determination of vigabatrin in human plasma by means of CE with LIF detection

Abstract: A method has been developed for the quantitation of the antiepileptic drug vigabatrin (VGB) in human plasma. It is based on CE with LIF detection. The effect of the pH of the buffer and of N-methylglucamine (GLC) as BGE constituent was investigated. The final BGE consisted of 50 mM borate buffer, pH 9.0, with 100 mM GLC and enabled separation within 12 min at 20 kV voltage. An SPE procedure was used for the pretreatment of biological samples, based on mixed-mode lipophilic-cation exchange cartridges, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Among them, the predominant reference methods that have become available for vigabatrin detection in clinical laboratories over the past 10-15 years are based on LC-FLD and LC-ESI-MS/MS techniques. However, there are some disadvantages in these methods, such as time-consuming operations for complex pre-column derivatization, [24][25][26][27][28][29][30][31] and the lengthy sample clean-up methods, such as liquid-liquid extraction 24 and solid-phase extraction, 26 consumption of the large plasma sample ($100 mL), 28,29,[32][33][34][35] and problems with low accuracy. 30 As shown in Table 1, the lowest lower limit of quantication was 0.04 mg mL −1 and the highest was 5 mg mL −1 , posing the problem of low sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, the predominant reference methods that have become available for vigabatrin detection in clinical laboratories over the past 10-15 years are based on LC-FLD and LC-ESI-MS/MS techniques. However, there are some disadvantages in these methods, such as time-consuming operations for complex pre-column derivatization, [24][25][26][27][28][29][30][31] and the lengthy sample clean-up methods, such as liquid-liquid extraction 24 and solid-phase extraction, 26 consumption of the large plasma sample ($100 mL), 28,29,[32][33][34][35] and problems with low accuracy. 30 As shown in Table 1, the lowest lower limit of quantication was 0.04 mg mL −1 and the highest was 5 mg mL −1 , posing the problem of low sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous works [21,22,24] we observed that the addition of amines, organic solvents or cyclodextrins (or a suitable combination of these additives) can improve the separation. We related the better resolution to the combined effects of the ionic strength [22] and the interaction of the analyte with the additive [21], but the reduction of the EOF played a role as well.…”
Section: Choice Of the Bgementioning
confidence: 98%
“…Elles concernent aussi bien le dosage de 5 antibiotiques [6], le dosage d'antirétro-viraux par HPLC/DAD [7] que le dosage de neuf antiépilep-tiques sur 100 μL de plasma [8], la cyclosporine sur 100 μL de plasma [9], du budénoside avec une limite de quantification de 50 pg/mL par LC/MS [10] ; le dosage de la simvastatine et de l'atorvastatine [11], du fentanyl avec une limite de quantification de 50 pg/mL par le couplage LC/MS/MS [12]. Le dosage du vigabatrin a également pu être réalisé par électrophorèse capillaire équipée d'un détecteur fluorescent [13].…”
Section: Applicationsunclassified